Desenvolvimento de uma metodologia para caracterização de amostras de sedimento: Rio Jundiaí RN - Lira, Débora de Carvalho (2008)
The study of sediment in water bodies presents great environmental importance, because of its ability to adsorb the pollutants, they may facilitate the understanding of the history of the current quality of the water system. Depending on how it is done the collection, analysis can show both a recent contamination as old. The detailed characterization of the sediment may reveal details that can understand how each type of pollutant interacts with the material given its composition. In this work it has developed a systematic methodology to characterize samples of sediment, with the aim to understand how a series of metal is distributed in different size fractions of the sediment. This study was conducted in five samples of sediment (P1, P2, P3a, P3B and P3c) collected in Jundiaí river, one of the most important tributaries of the river Potengi in the region of Macaíba, RN. The characterization was made with the samples previously sieved into meshes with different granulometries (+8#, -8+16#, -16+65# - 65+100#,-100+200#,-200+250# and -250#), using the following techniques: Analysis of specific surface area by BET method, determining the levels of organic matter (OM%) and humidity through the gravimetry and Analysis Thermogravimetric (TG), Infrared Spectroscopy in a Fourier transform (FTIR ), Analysis of X ray diffraction (XRD), analysis of heavy metals by optical emission spectrometry with the Argon Plasma (ICP-OES). The analyzed elements were Al, Cd, Cr, Cu, Fe, Mn, Ni, Zn and P. In addition to the techniques of characterization above, was also made the rebuilding of the samples P1, P2 and P3B in relation to the levels of organic matter and concentration of heavy metals. Then, the results of the recomposed samples were compared with those obtained in crude samples, showing great consistency. The gravimetry, used in determining the levels of organic matter, was not considered an appropriate method because the clay minerals present in the sediment samples analyzed fall apart in the same range of temperature (550-600 0C) used in roasting (600 0C). The results also showed the trend of organic matter and heavy metals to focus on the thin fractions, although the largest concentrations of metals are in intermediate fractions